Capacity strengthening strategy through capacity needs assessment for Country Level Strategic Analysis and Knowledge Support System (SAKSS): Zambia - Musonda, Doris; Maroeidi, Vasiliki; Tembo, Stephen; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso B.; Chikwenya, Nicholas; Sikombe, Derrick; Chilonda, Pius (International Food Policy Research Institute, 2014)
The overall goal of the capacity needs assessment was to collect qualitative and quantitative data from key institutions involved in the food and agricultural policy process that would be used to inform a capacity strengthening strategy (CSS) for Zambia to meet the strategic analysis and knowledge management needs of the country Comprehensive Africa Agriculture Development Programme (CAADP) process. The assessment was undertaken at three different levels: country, organizational, and individual. Data were collected at all three levels through a series of key informant interviews and the distribution of a detailed survey to 11 key institutions that are involved in the food and agricultural policy process in Zambia. Data collection was undertaken between June and August 2013.